1993
DOI: 10.2307/1940842
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Transplant Reveals Sources of Variation in Growth Rates of the Lizard Sceloporus Undulatus

Abstract: Geographic variation in life history phenotypes between populations of a single species is often assumed to reflect genetic divergence caused by natural selection. The relative contribution of genetic and environmental sources of phenotypic variation is rarely determined, especially for vertebrates. However, distinguishing between phenotypic plasticity induced by proximate environmental variation and genetic divergence is fundamental to understanding the ecological and evolutionary significance of geographic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
144
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(162 citation statements)
references
References 43 publications
12
144
1
5
Order By: Relevance
“…In contrast to previous studies that documented metabolic differences between closely related study groups (e.g., Niewiarowski and Roosenburg 1993;Klaassen 1995;Mueller and Diamond 2001;Wikelski et al 2003;Broggi et al 2004Broggi et al , 2005Tieleman 2007), we found no evidence of intrinsic differences in basic metabolic parameters between C. p. ptilocnemis and C. p. tschuktschorum held under identical conditions. There was no variation in BMR or thermal conductance of Rock Sandpipers by sex or subspecies, and the metabolic response of each subspecies to temperature did not differ.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies that documented metabolic differences between closely related study groups (e.g., Niewiarowski and Roosenburg 1993;Klaassen 1995;Mueller and Diamond 2001;Wikelski et al 2003;Broggi et al 2004Broggi et al , 2005Tieleman 2007), we found no evidence of intrinsic differences in basic metabolic parameters between C. p. ptilocnemis and C. p. tschuktschorum held under identical conditions. There was no variation in BMR or thermal conductance of Rock Sandpipers by sex or subspecies, and the metabolic response of each subspecies to temperature did not differ.…”
Section: Discussioncontrasting
confidence: 99%
“…Comparisons between closely related species, subspecies, or populations with divergent life-history traits can help discern the contributions of genes and environment in determining basic metabolic and physiological variables (Mueller andDiamond 2001, Wikelski et al 2003). Previous comparisons across a wide array of taxa have investigated a variety of physiological parameters, including metabolic rate (Klaassen 1995, Piersma 1996, immune response (Buehler et al 2009), total evaporative water loss (Williams et al 2004, Tieleman 2007, growth rate (Niewiarowski and Roosenburg 1993), digestive function (Mueller and Diamond 2001;van Gils et al 2005a, b), and thermal conductance (Scholander et al 1950a, b). Despite numerous studies, however, no predictable patterns have emerged to show how phenotypically flexible traits are modulated across taxa.…”
Section: La Tasa Metabólica Y La Conductancia Térmica Son Idénticas Ementioning
confidence: 99%
“…We assumed that variation among taxa included in the analysis represented population-specific differences not attributable to simple phenotypic plasticity arising from temporal variation in environmental factors. We cannot directly test the validity of this assumption, but several experimental studies with S. undulatus have demonstrated that there are significant population-specific sources of variation in life-history traits that are not attributable to proximate environmental effects (Ferguson and Brockman 1980;Ferguson and Talent 1992;Niewiarowski and Roosenburg 1993).…”
Section: Life-history Datamentioning
confidence: 99%
“…Perhaps no other species of lizard has received as much attention in this regard as Sceloporus undulatus, which has been the subject of numerous statistical and theoretical analyses of geographic variation in life-history traits (e.g., Tinkle and Ballinger, 1972;Tinkle and Dunham, 1986;Gillis and Ballinger, 1992; Adolph and Porter, 1993, 1996;Niewiarowski, 1994;Smith et al, 1996). More recently, populations of S. undulatus have been the focus of more experimental investigations into the causes of such geographic variation (e.g., Ferguson and Talent, 1993;Niewiarowski and Roosenburg, 1993;Niewiarowski, 1995Niewiarowski, , 2001 Angilletta, 2001a,b).Although S. undulatus has served as a model organism for studying geographic variation, much of the information used in these analyses has come from North American populations and subspecies. Relatively little detailed information is known about the biology and ecology of the Mexican populations and subspecies of S. undulatus (but for studies on Sceloporus belli, formerly Sceloporus undulatus belli in Durango, México, see Barbault et al, 1978;Barbault and Maury, 1981; Gadsden-Esparza and Aquirre-León, 1993).…”
mentioning
confidence: 99%
“…For example, diet and body temperature are remarkably similar, especially considering the geographic range encompassed by this species. However, traits such as clutch size, size at sexual maturity, and sexual dimorphism vary substantially, as does growth rate (see Niewiarowski and Roosenburg, 1993). Despite the fact that several populations of S. undulatus have been studied, we rarely have detailed information on several aspects of each population's ecology (e.g., we know a lot about a population's clutch size, but little on body temperature, perch use, or diet).…”
mentioning
confidence: 99%